USM SCIENTISTS COMMITTED TO CONTRIBUTING MORE TO THE NATION - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PUTRAJAYA, 1 November 2016 – Three scientists from Universiti Sains Malaysia (USM) did the University proud when they were selected as recipients of the prestigious Malaysia's Rising Star Award 2016 for various categories in a ceremony graced by the Minister of Higher Education, Dato' Seri Idris Jusoh, who gave away the awards here today.